Innovative Diagnostics and Treatment: Nanorobotics and Stem Cells - Jadczyk, Tomasz; Tfaily, Ewa Bryndza; Mishra, Sachin; Jędrzejek, Marek; Bołoz, Marta; Padmanabhan, Parasuraman; Wojakowski, Wojciech; Stárek, Zdeněk; Martel, Sylvain; Gulyás, Balázs; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on nanorobotic agents and stem cells for biomedical applications.It is intended for researchers and clinicians interested in innovative diagnostic and therapeutic strategies based on nanorobots and stem cells.It presents current advances in the field of molecular machines, which could be applied to generate novel therapeutic-diagnostic systems.
1. Introduction. - 2. Integrated therapeutic-diagnostic systems for cancer and cardiovascular diseases -- 3. Nanorobotic agents -- 4. Application of nanorobots for nanotheranostics.
Keywords: Biomedical engineering; Cancer; Cardiology; Microtechnology; Microelectromechanical systems; Medicine -- Research; Biology -- Research; Biomaterials; Biomedical Engineering and Bioengineering; Cancer Biology; Cardiology; Microsystems and MEMS; Biomedical Research; Biomaterials